LEXIS DEVELOPMENT: THE IMPORTANCE OF CONTEXTUAL CLUES - Abdelaziz Ahmed, Awwad Osman (European Scientific Journal, ESJ, 2013)
Lexis development has become an important part of second language acquisition. Students need to be taught vocabulary in context so that they can retain the words and use them frequently. The present study is carefully designed to gain insight into the effects of context on lexis learning. It reflects that illustrations of words in various sentences are more helpful to students than lexical explanations. Therefore, the researcher suggests that the best way of teaching new words is to put them into a variety of defining contexts. In this way, students can master various syntactic and semantic uses of words in authentic English sentences. Some important strategies and techniques that can help facilitate the acquisition and development of English lexis are investigated.